Hypocenter migration and crustal seismic velocity distribution observed for the inland earthquake swarms induced by the 2011 Tohoku‐Oki earthquake in NE Japan: implications for crustal fluid distribution and crustal permeability. Issue 1 (30th September 2014) - Okada, T.; Matsuzawa, T.; Umino, N.; Yoshida, K.; Hasegawa, A.; Takahashi, H.; Yamada, T.; Kosuga, M.; Takeda, T.; Kato, A.; Igarashi, T.; Obara, K.; et al.
Abstract: After the occurrence of the 2011 magnitude 9 Tohoku earthquake, the seismicity in the overriding plate changed. The seismicity appears to form distinct belts. From the spatiotemporal distribution of hypocenters, we can quantify the evolution of seismicity after the 2011 Tohoku earthquake. In some earthquake swarms near Sendai (Nagamachi‐Rifu fault), Moriyoshi‐zan volcano, Senya fault, and the Yamagata–Fukushima border (Aizu‐Kitakata area, west of Azuma volcano), we can observe temporal expansion of the focal area. This temporal expansion is attributed to fluid diffusion. Observed diffusivity would correspond to the permeability of about 10 −15 (m 2 ). We can detect the area from which fluid migrates as a seismic low‐velocity area. In the lower crust, we found seismic low‐velocity areas, which appear to be elongated along N–S or NE–SW, the strike of the island arc. These seismic low‐velocity areas are located not only beneath the volcanic front but also beneath the fore‐arc region. Seismic activity in the upper crust tends to be high above these low‐velocity areas in the lower crust. Most of the shallow earthquakes after the 2011 Tohoku earthquake are located above the seismic low‐velocity areas. We thus suggest fluid pressure changes are responsible for the belts of seismicity. Abstract : Temporal expansion of the focal area in some earthquake swarms near Sendai (Nagamachi‐Rifu fault), Moriyoshi‐zan volcano, Senya fault, and the Yamagata‐Fukushima border (Aizu‐Kitakata area, west of Azuma volcano) induced by the 2011 Tohoku‐Oki earthquake was observed. This temporal expansion can be explained by fluid diffusion. We found seismic low‐velocity areas, which is the possible areas with fluid, beneath the swarms. From the results, the induced earthquakes are thought to be affected by the possible fluid pressure change.